A study on knowledge attitude and practices related to hepatitis B infection among nursing students of government nursing college, Jagdalpur, Bastar, Chhattisgarh - Nalli, Susheel Kumar; Sinha, Teeku; Arora, Garima; Khan, Qamrul H. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hepatitis-B virus is a potentially critical and familiar occupational hazard for health care workers including nursing students particularly those who are exposed to the populations whose HBsAg prevalence is high. The aim of the study was to assess the Hepatitis-B - knowledge, perception and vaccination status among nursing students. Methods: A cross-sectional study was conducted by Department of Community Medicine, Government Medical College, Jagdalpur, Chhattisgarh in July 2016, among nursing students of Government Nursing College, Jagdalpur, Chhattisgarh. Using purposive sampling data was collected via a pre-tested self- administered questionnaire. Overall 218 nursing students participated in the study. Statistical analysis was done using Stata version 12.1. Chi square test was used to identify any statistically significant difference among the nursing batches. Results: The study found that only 18.9% of the 1st year students are vaccinated. Knowledge regarding treatment options was found out to be significantly (p<0.05) low among all nursing batches. Conclusions: There is lack of knowledge among all students regarding its treatment. Only 18.97% of the 1st year students reported to be vaccinated which puts them at a greater risk of acquiring the infection in future. Therefore, it is recommended that they should get themselves vaccinated before entering clinical rotations. More studies should be conducted on nursing/ medical staff to assess their knowledge on Hepatitis B infection in tribal areas which have high prevalence.